Four-Tier Diagnostic Test with Certainty of Response Index to Identify Misconception in Physics - Yuberti, Yuberti; Suryani, Yani; Kurniawati, Indah (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aimed to develop a Four-Tier Test diagnostic test instrument that will be used to identify student misconceptions on work and simple machine topic. This research is a development research using the ADDIE model. The result of the research is a multiple-choice test instrument four-tier diagnostic test with the Certainty of Response Index (CRI) to identify misconceptions. The results of expert validation show that the questions are declared valid. Furthermore, the instrument was tested on grade VIII students of SMP Negeri 1 Kalirejo to determine the level of validity, reliability, difficulty, and differentiation on each item. Of the 20 items developed, 15 of them were declared feasible to identify student misconceptions